Job Creation in a Multi-Sector Labor Market Model for Developing Economies - Arnab K. Basu; Nancy Chau; Gary S. Fields; Ravi Kanbur (Institute for the Study of Labor (IZA), 2016)
This paper proposes an overlapping generations multi-sector model of the labor market for developing countries with three heterogeneities – heterogeneity within self-employment, heterogeneity in ability, and heterogeneity in age. We revisit an iconic paradox in a class of multi-sector labor market models in which the creation of high-wage employment exacerbates unemployment. Our richer setting allows for generational differences in the motivations for job search to be reflected in two distinct inverted U-shaped relationships between unemployment and high-wage employment, one for youth and a different one for adults. In turn, the relationship between overall unemployment and high-wage employment is shown to be non-monotonic and multi-peaked. The model also sheds light on the implications of increasing high-wage employment on self-employed workers, who make up most of the world's poor. Non-monotonicity in unemployment notwithstanding, increasing high-wage employment has an unambiguous positive impact on high-paying self-employment, and an unambiguous negative impact on free-entry (low-wage) self-employment.
Keywords: O17; I32; 330; multisector labor market; overlapping generations; poverty reduction; Harris-Todaro model